Reinventing appraisal - Kate Cumming; Anne Picot (Archives & Manuscripts, 2014)
In 1986 David Bearman first put the argument that core archival methods of appraisal, description, preservation and access were fundamentally unable to cope with the volumes of records archivists were required to process. He called on the archival profession to completely reinvent its core methods. Noting similar challenges for archival methods in evolving digital business environments, this paper explores how the archival method of appraisal could be reinvented.